2022
DOI: 10.1158/1078-0432.ccr-22-1449
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 First-in-Human Study of FS118, a Tetravalent Bispecific Antibody Targeting LAG-3 and PD-L1 in Patients with Advanced Cancer and PD-L1 Resistance

Abstract: Purpose: This Phase 1 study (NCT03440437) evaluated the safety, tolerability, pharmacokinetics and activity of FS118, a bispecific antibody targeting LAG-3 and PD-L1, in patients with advanced cancer resistant to anti-PD-(L)1 therapy. Experimental Design: Patients with solid tumors, refractory to anti-PD-(L)1-based therapy, received intravenous FS118 weekly with an accelerated dose titration design (800 µg to 0.3 mg/kg) followed by 3+3 ascending dose expansion (1 mg/kg to 20 mg/kg). Primary objectives were saf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…FS118 binds both LAG-3 and PD-L1, blocking PD-1/PD-L1, CD80/PD-L1, and LAG-3/MHC-II interactions, thereby reversing T cell suppression and promoting the production of cytokines by CD4 + and CD8 + T cells [ 187 ]. A Phase I clinical trial (NCT03440437) for patients with advanced cancers and PD-L1 drug resistance initially showed that FS118 was well tolerated, but further studies are needed to determine the clinical benefit for patients refractory to anti-PD-(L)1 therapy [ 188 ]. IBI323 demonstrated similar potency in blocking the interactions of PD-1/PD-L1, CD80/PD-L1, and LAG-3/MHC-II.…”
Section: Other Approaches To Targeting Lag-3 Tim-3 and Tigit For Immu...mentioning
confidence: 99%
“…FS118 binds both LAG-3 and PD-L1, blocking PD-1/PD-L1, CD80/PD-L1, and LAG-3/MHC-II interactions, thereby reversing T cell suppression and promoting the production of cytokines by CD4 + and CD8 + T cells [ 187 ]. A Phase I clinical trial (NCT03440437) for patients with advanced cancers and PD-L1 drug resistance initially showed that FS118 was well tolerated, but further studies are needed to determine the clinical benefit for patients refractory to anti-PD-(L)1 therapy [ 188 ]. IBI323 demonstrated similar potency in blocking the interactions of PD-1/PD-L1, CD80/PD-L1, and LAG-3/MHC-II.…”
Section: Other Approaches To Targeting Lag-3 Tim-3 and Tigit For Immu...mentioning
confidence: 99%
“…Moreover, binding of the surrogate mLAG-3/PD-L1 antibody resulted in the rapid shedding of mouse LAG-3 into the blood [ 130 ]. In clinical studies, a phase 1 trial (NCT03440437) demonstrated the safety and tolerability of FS118 in patients with advanced, anti-PD-1/PD-L1-resistant cancers [ 131 ]. FS118 showed a recommended phase 2 dose of 10 mg/kg weekly, sustained pharmacodynamic activity, and an overall disease control rate of 46.5%, particularly notable in patients with acquired resistance to PD-1/PD-L1-targeted therapy [ 131 ].…”
Section: Anti-lag-3 × Pd-l1 Bsabmentioning
confidence: 99%
“…In clinical studies, a phase 1 trial (NCT03440437) demonstrated the safety and tolerability of FS118 in patients with advanced, anti-PD-1/PD-L1-resistant cancers [ 131 ]. FS118 showed a recommended phase 2 dose of 10 mg/kg weekly, sustained pharmacodynamic activity, and an overall disease control rate of 46.5%, particularly notable in patients with acquired resistance to PD-1/PD-L1-targeted therapy [ 131 ]. This study supports the continued investigation of FS118 for patients with refractory cancers, highlighting its potential as an effective dual PD-L1 × LAG-3 blockade strategy.…”
Section: Anti-lag-3 × Pd-l1 Bsabmentioning
confidence: 99%
“…The following supporting information can be downloaded at https:// www.mdpi.com/article/10.3390/cancers16020335/s1, Table S1: Clinical trials of bispecific antibodies for advanced solid tumors including metastatic urothelial carcinoma; Table S2: Clinical trials of cellular therapies in advanced solid tumors including metastatic urothelial carcinoma; Table S3: Clinical trials of vaccines and oncolytic viruses in advanced solid tumors including metastatic urothelial carcinoma. References [124,[147][148][149][150][151][152][153][154][155][156][157][158][159][160] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%